Impact of magnetic dipole on ferromagnetic hybrid nanofluid flow over a stretching cylinder. (12th February 2021) - Kumar, R Naveen; Gowda, R J Punith; Abusorrah, Abdullah M; Mahrous, Y M; Abu-Hamdeh, Nidal H; Issakhov, Alibek; Rahimi-Gorji, Mohammad; Prasannakumara, B C
Abstract: Nanofluids manage heat in the internal combustion of the engines or machines by avoiding corrosion in the cooling system as well as assist in eradicating the engine's waste heat. Hence, they are used as coolants in many automotive industries. Inspired by these applications, the thermal and mass transfer in hybrid nanoliquid flow over a stretching cylinder on taking account of magnetic dipole is studied in this investigation. Here, we have done a comparative study on flow of two diverse combinations of hybrid nanofluids, namely MnZnFe 2 O 4 − NiZnFe 2 O 4 − C 10 H 22 and Cu − Al 2 O 3 − C 10 H 22 . The modelled equation for the assumed flow is converted to ODEs by opting appropriate similarity variables. These ODEs are solved by utilizing the Runge–Kutta Fehlberg fourth-fifth order (RKF-45) method by adopting shooting technique. Physical clarification of relevant parameters for non-dimensional discrete flow fields are discussed briefly by using graphs. Also, skin friction, Sherwood and Nusselt numbers are deliberated with the assistance of graphs. Results reveal that, the upsurge in ferromagnetic interaction parameter declines the velocity in both fluids but converse trend is detected in temperature and concentration of the liquids. The heightening of ferromagnetic interaction parameter declines the rate of heat and mass transfer.